2022
DOI: 10.3390/toxins14050331
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Exposure and Risk Assessment of Mycotoxins in Thyme and Thyme-Based Products Marketed in Lebanon

Abstract: This study aimed at evaluating the incidence of aflatoxin B1 (AFB1) and ochratoxin A (OTA) in thyme and thyme-based products, related dietary exposure, and cancer risk for regular and high consumption. A total of 160 samples were collected, and 32 composite samples were analyzed. AFB1 and OTA were respectively found in 84% (27/32) and 38% (12/32) of the samples. AFB1 exceeded the limits in 41% (13/32) and 25% (8/32) of the samples according to the Lebanese and European standards, respectively. OTA was unaccept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Consequently, the exposure to AFB1 in this study was associated with 0.105 additional liver cancer cases/100,000 people/year, greater than the risk observed in studies by Raad et al of 0.053–0.055 additional liver cancer cases/100,000 people/year for regular consumers [ 15 ] and Daou et al (0.076 HCC/100,000 people/year) [ 11 ] but less than that reported Hassan et al (0.35–0.41 HCC/100,000 people/year) [ 31 ]. OTA had an exposure of 4.10 ng/kg bw/day, higher than the exposure level reported in other Lebanese studies, such as one conducted by Hassan et al (1.345 ng/kg bw/day) [ 31 ]; however, it was lower than that reported by Raad et al (4.28 ng/kg bw/day) [ 15 ] and Daou et al (7.60 ng/kg bw/day) [ 11 ]. For AFM1, the total exposure (0.39 ng/kg bw/day) was greater than the level obtained from a study by Hassan et al (0.14 ng/kg bw/day) [ 32 ].…”
Section: Discussionmentioning
confidence: 82%
“…Consequently, the exposure to AFB1 in this study was associated with 0.105 additional liver cancer cases/100,000 people/year, greater than the risk observed in studies by Raad et al of 0.053–0.055 additional liver cancer cases/100,000 people/year for regular consumers [ 15 ] and Daou et al (0.076 HCC/100,000 people/year) [ 11 ] but less than that reported Hassan et al (0.35–0.41 HCC/100,000 people/year) [ 31 ]. OTA had an exposure of 4.10 ng/kg bw/day, higher than the exposure level reported in other Lebanese studies, such as one conducted by Hassan et al (1.345 ng/kg bw/day) [ 31 ]; however, it was lower than that reported by Raad et al (4.28 ng/kg bw/day) [ 15 ] and Daou et al (7.60 ng/kg bw/day) [ 11 ]. For AFM1, the total exposure (0.39 ng/kg bw/day) was greater than the level obtained from a study by Hassan et al (0.14 ng/kg bw/day) [ 32 ].…”
Section: Discussionmentioning
confidence: 82%
“…Accumulating research has implicated the existence of these toxic heavy metals in many food matrices beyond permissible limits [19] , [20] . Dghaim et al conducted a study on traditional herbs found in the UAE market and showed that the maximum level of Cd in oregano and thyme samples were 0.35 mg/kg and 0.63 mg/kg, respectively, thus exceeding the permissible limit of cadmium 0.3 mg/kg set by the FAO/WHO [6] .…”
Section: Resultsmentioning
confidence: 99%
“…Factors such as model interpretability, integration with existing health IT systems, and adherence to regulatory standards are critical for successful implementation ( 41 ). Future endeavors could center on multi-class classification to differentiate between various types of breast cancer, thereby expanding the model’s applicability in clinical diagnostics ( 42 ). Furthermore, assessing the model’s performance on external datasets and in real-world clinical environments would be crucial to validate its applicability and robustness further.…”
Section: Discussionmentioning
confidence: 99%